17β‐oestradiol enhances global DNA hypomethylation in CD4‐positive T cells from female patients with lupus, through overexpression of oestrogen receptor‐α‐mediated downregulation of DNMT1. (1st June 2014) - Wu, Z.; Sun, Y.; Mei, X.; Zhang, C.; Pan, W.; Shi, W.
Summary: Background: Systemic lupus erythematosus (SLE) affects primarily women, and oestrogen appears to play a significant role in SLE development. Our previous studies showed that inhibition of DNA methyltransferase 1 (DNMT1) enhanced global DNA hypomethylation in CD4+ T cells isolated from patients with SLE, and exacerbated SLE. However, the effects of 17β‐oestradiol on global DNA hypomethylation and DNMT1 expression in CD4+ T cells of female patients with SLE remain largely unknown. Aim: To investigate the ability of 17β‐oestradiol to affect global DNA methylation in female SLE CD4+ T cells and the mechanism(s) underlying this ability. Methods: We enrolled 30 women with SLE and 15 controls. CD4+ T cells exposed to 17β‐oestradiol were analysed by global DNA methylation measurements, western blotting and real‐time PCR. Plasma 17β‐oestradiol levels were measured by ELISA. Results: In female SLE CD4+ T cells, 17β‐oestradiol downregulated DNMT1 expression at both the mRNA and protein levels, and enhanced global DNA hypomethylation. Plasma 17β‐oestradiol levels were similar in patients with SLE and controls. The mRNA expression of oestrogen receptor (ER)α, but not of ERβ, was upregulated in SLE CD4+ T cells. Furthermore, the 17β‐oestradiol‐induced downregulation of DNMT1 expression and global DNA hypomethylation were rescued by an ER antagonist. Conclusions: 17β‐oestradiol enhances global DNA hypomethylation in female SLE CD4+ T cells via downregulation of DNMT1 mediated by ERα overexpression.